2020
DOI: 10.5195/jyd.2020.847
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Outcomes and Impact: The Contributions and Consequences of Volunteering in 4-H

Abstract: Youth development volunteers are relied upon by many youth organizations to deliver educational programming, and consequently, fulfill organizations’ missions. Our study explored the consequences of volunteering in youth services by focusing on volunteer outcomes (consequences of volunteering on the volunteer) and volunteer impacts (volunteers’ contributions to the organization). We collected 1,245 open-ended responses to 2 questions from adults who served as volunteers in the University of California 4-H Yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…Previous studies have reported benefits of volunteering, especially for older adults, suggesting improved psychological well-being [ 27 ], physical health [ 28 ], quality of life [ 29 ], mental health, and reduced depression symptoms [ 11 ]. Other studies have highlighted the importance of volunteering in forming social connections and meaningful social relationships [ 11 , 12 , 30 ]. This aligns with our result of improved personal relationships after the volunteering experience, since this enhanced connection with others assists the formation of new relationships and strengthens previous ones, such as family connections and community ties [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported benefits of volunteering, especially for older adults, suggesting improved psychological well-being [ 27 ], physical health [ 28 ], quality of life [ 29 ], mental health, and reduced depression symptoms [ 11 ]. Other studies have highlighted the importance of volunteering in forming social connections and meaningful social relationships [ 11 , 12 , 30 ]. This aligns with our result of improved personal relationships after the volunteering experience, since this enhanced connection with others assists the formation of new relationships and strengthens previous ones, such as family connections and community ties [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the implementation of specific program practices may significantly influence the nature of the volunteer mentor experience (see Herrera et al, 2013;Kupersmidt et al, 2017) and also influence how a sustaining and effective volunteer engagement gets established (Haski-Leventhal & Bargal, 2008;Malinen & Harju, 2017). Many mentoring programs devote considerable effort to recruiting volunteers, but actually retaining those volunteers is critical for mentoring relationships to last long enough to have positive effects in working with young people (Grossman et al, 2012;Grossman & Rhodes, 2002;Stukas et al, 2014), such as strengthening the supported young people's capabilities (Grant et al, 2020, p. 38;Worker et al, 2020). In youth work-related fields and in multicomponent program settings, volunteers wish to have training that would help to increase their content knowledge on youth and youth development skills (Hensley et al 2020;Kok et al, 2020;Plourde et al, 2021).…”
Section: Volunteering Is More Than Motivation and Benefitsmentioning
confidence: 99%
“…However, research has shown that people are motivated to volunteer also to grow and satisfy personal psychological needs [ 6 , 7 , 8 ]. Evidence exists that volunteering may promote the volunteers’ benefits in terms of physical, social, and psychological health [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Most studies have focused only on the beneficial effects of engaging in volunteering, whereas individual characteristics that may contribute to volunteers’ psychological health have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%